Breathing and Range of Motion Exercises as Fatigue Intervention In Chronic Kidney Failure Patients: a Case Study - Renandha Parahita; Dian Hudiyawati (International Journal of Health and Medicine, 2024)
Background : One of the most prominent negative impacts in patients with kidney failure undergoing hemodialysis is fatigue. Breathing and range of motion exercises are therapies that can be applied to reduce fatigue in patients with chronic kidney failure. Objective: to provide breathing and range of motion exercise interventions in patients with chronic renal failure. Method: used in this study is a case study. Assessment of Mrs. S conducted for 3 consecutive days. Results: After the intervention for 3 days, the results showed that the level of fatigue and anxiety in Mrs. S decreased. Conclusions and suggestions: The interventions given have an effect on reducing the level of anxiety and fatigue of patients. It is expected that nurses can provide optimal nursing care to patients with chronic kidney failure to improve the quality of life of patients.